2007
DOI: 10.1089/dna.2006.0505
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Osteosarcoma

Abstract: Osteosarcoma is a devastating but rare disease, whose study has illuminated both the basic biology and clinical management of cancer over the past 30 years. These contributions have included insight into the roles of key cancer genes such as the retinoblastoma tumor suppressor gene and TP53, the identification of familial cancer syndromes implicating DNA helicases, and dramatic improvements in survival by the use of adjuvant chemotherapy. This review provides a synoptic overview of our current understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
243
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(248 citation statements)
references
References 199 publications
3
243
2
Order By: Relevance
“…osx-cre ͉ Sca-1 ͉ hibernoma mouse model O steosarcomas account for Ϸ30% of malignant bone tumors and 3-4% of all childhood malignancies (1,2). They arise primarily around the knee joint, lower femur and upper tibia, which are all regions of active bone growth and repair.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…osx-cre ͉ Sca-1 ͉ hibernoma mouse model O steosarcomas account for Ϸ30% of malignant bone tumors and 3-4% of all childhood malignancies (1,2). They arise primarily around the knee joint, lower femur and upper tibia, which are all regions of active bone growth and repair.…”
mentioning
confidence: 99%
“…However, like other mesenchymal neoplasms, osteosarcomas are predisposed to metastasize via the hematogenous route, and thus, pulmonary metastasis is a major cause of death. Analyses of both sporadic and hereditary tumors show that inactivation of the p53 and RB-1 tumor suppressors plays a key role in the development of this tumor type (1,2). Li-Fraumeni patients, who often carry germ-line mutations in p53, are predisposed to a variety of tumors, 12% of which are bone sarcomas (3,4).…”
mentioning
confidence: 99%
“…5 Gene expression and proteomic studies have identified the possible role of ezrin in metastasis. 6,7 The identification of ezrin expression is a necessary component in osteosarcoma metastasis and it makes the study of this protein crucial in understanding the molecular pathways involved in metastatic diffusion.…”
mentioning
confidence: 99%
“…It transactivates genes that encoded apoptotic proteins, and it translocates to mitochondria where it interacts with Bcl-2 proteins (Moll et al, 2001). Many OSAs exhibit p53 abnormalities, and mice expressing p53-null osteoblast progenitor cells will develop OSAs (Lengner et al, 2006;Kansara et al, 2007). Suggesting that Bcl-2 proteins are important for the regulation of the p53 in the OSA.…”
Section: Cdks Play An Import Role In the Pathogenesis Of The Osamentioning
confidence: 99%